KNOWLEDGE OF PATIENTS WITH DIABETES MELLITUS ABOUT DIABETES NEUROPATHY SYMPTOMS - Joeliantina, Anita; Zahratul, Sintya; Hasanah, Nur; Wuryaningsih, Sri Hardi; Soelistyowati, Endang (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Diabetes Mellitus (DM) is a metabolic disease characterized by high blood glucose levels or hyperglycemia, which in the long term can cause complications both macrovascular and microvascular. Diabetic Neuropathy (ND) is one of the many complications experienced by patients with DM. Objectives: This study aimed to determine the level of knowledge of patients with DM about ND symptoms at Community Health Center Pacarkeling Surabaya. Methods: This study used a descriptive research method with a cross-sectional approach. A large sample of 100 adult patients with DM. A purposive sampling technique was used. The instrument of this study was a questionnaire. Data analysis used descriptive analysis with frequency distribution tables. Results: This study showed that most respondents (65%) had less knowledge about ND symptoms, and almost all patients had foot complaints. The most complaints were 98% complaining of tingling feet and 75% complaining of numb feet. Data characteristics of respondents showed that 45% of patients were 56-65 years old, 68% were female, 41% had junior high school education, and 55% were not working. Other data show 86% of patients have a duration of DM of <10 years, the treatment used was 77% taking oral antidiabetic drugs, and 68% have a history of heredity. Conclusion: Patients with DM in research have a risk of developing diabetic foot ulcers because they have reduced knowledge and foot complaints related to ND. Patients must know the signs and symptoms of ND and foot care correctly. As part of the health staff, nurses must educate patients with DM regularly and appropriately.